Emerging Roles of Sodium Glucose Cotransporter 2 (SGLT-2) Inhibitors in Diabetic Cardiovascular Diseases: Focusing on Immunity, Inflammation and Metabolism - Xie, Lingxiang; Xiao, Yang; Tai, Shi; Yang, Huijie; Zhou, Shenghua; Zhou, Zhiguang (Frontiers in Pharmacology, 2022)
Diabetes mellitus (DM) is one of the most fast evolving global issues characterized by hyperglycemia. Patients with diabetes are considered to face with higher risks of adverse cardiovascular events. Those are the main cause of mortality and disability in diabetes patients. There are novel antidiabetic agents that selectively suppress sodium-glucose cotransporter-2 (SGLT-2). They work by reducing proximal tubule glucose reabsorption. Although increasing evidence has shown that SGLT-2 inhibitors can contribute to a series of cardiovascular benefits in diabetic patients, including a reduced incidence of major adverse cardiovascular events and protection of extracardiac organs, the potential mechanisms of SGLT2 inhibitors’ cardiovascular protective effects are still not fully elucidated. Given the important role of inflammation and metabolism in diabetic cardiovascular diseases, this review is intended to rationally compile the multifactorial mechanisms of SGLT-2 inhibitors from the point of immunity, inflammation and metabolism, depicting the fundamental cellular and molecular processing of SGLT-2 inhibitors exerting regulating immunity, inflammation and metabolism. Finally, future directions and perspectives to prevent or delay cardiovascular complications in DM by SGLT-2 inhibitors are presented.